"What happens behind the curtains?" An exploration of ICU nurses' experiences of post mortem care on patients who have died in intensive care. (December 2017) - de Swardt, Carien; Fouché, Nicola
Abstract: The Aim of the Study: The aim of this study was to explore the experiences of intensive care nurses performing post mortem care on patients who had died in an intensive care unit at a private hospital in Cape Town. The study further sets out to identify educational needs and to offer recommendations that may address these needs for this sample of nurses. Methodology and setting: A qualitative research design using a descriptive method was used to explore the experiences of a purposive heterogeneous sample of six nurses who were working in an intensive care unit in a private hospital in Cape Town. Data collection and analysis: A semi-structured interview which was audio-taped and transcribed verbatim was employed to collect data. Colaizzi's (1978) seven step inductive method was used to formulate naïve themes. Following participant feedback, three main themes emerged: care of the dead body, detachment and thanatophobia. Findings: Safeguarding the integrity and physical appearance of the dead body was the major finding and of the utmost priority for the participants in this study. Regardless of how the nurses felt about death, providing professional and quality care to the dead body and the family was seen as significantly important. The nurses, whilst performing post mortem care, experienced detachment from various relationships. This comprised of the nurse detaching him/herself professionally and emotionally from the dead patient, the family and him/herself from the death experience. This 'unspoken' experience of thanatophobia became apparent when the nurses were confronted by the reality of their own deaths. Conclusion and recommendations: In a technological society, where answers to many questions can be pursued through science, understanding the experience of death, as opposed to dying, may be logically incomprehensible. Death remains one of the most traumatic events experienced by the patient and their family, and in some instances nurses themselves. The study has drawn attention to the nurses' experiences and in doing so; the emotional and educational needs have been identified, and in part, pedagogical offerings are recommended.